Simultaneous Estimation of Simvastatin and Ezetimibe in Tablet Formulations - R. KARAJGI, SANTOSH; SIMPI, C.C. (Asian Journal of Chemistry, 2010)
An accurate and economical procedure for the simultaneous estimation of simvastatin and ezetimibe in tablet formulation has been developed. The method involves the solving of simultaneous equations. Simvastatin has absorbance maxima at 242 nm in chloroform and ezetimibe has absorbance maxima at 248 nm in chloroform. Both these drugs obey Beer's law in concentration ranges employed for the present method. The result of analysis has been validated statistically by recovery studies.